2009
DOI: 10.3846/1611-1699.2009.10.85-97
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Boundaries on Mentoring: Can Mentoring Be a Knowledge Tool?

Abstract: Abstract. Easy access to organizational knowledge is fundamental in dynamic environments that demand continuous fi rm adaptation. In that scenario we believe that mentors have a key role as access facilitators to knowledge in the change periods. We have developed this study aiming to explore the role and importance of mentors as knowledge access facilitators. We have approached that role in two different ways. We set apart the knowledge base in two categories: Information centers and organizational memory, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…They suggested that this configuration might lead to bidirectional learning. Henriques and Curado () found that a mentor functioned as a knowledge‐accessing tool. This function facilitated the transfer of organizational knowledge to the protégé.…”
Section: Review Of Literaturementioning
confidence: 99%
“…They suggested that this configuration might lead to bidirectional learning. Henriques and Curado () found that a mentor functioned as a knowledge‐accessing tool. This function facilitated the transfer of organizational knowledge to the protégé.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Lessons learnedregular meetings to discuss successes and failures in relation to a process and product, providing learning and identifying lessons that can be useful for other situations Process Benbya and Benbya, 2005;Binney, 2001;Bollinger and Smith, 2001;Davenport et al, 1998;Jarrar, 2002;Saito et al, 2007 Mentoringan individual with more experience in the organization contributes to the personal development of individuals with less experience in the organization Process Arling and Chun, 2011;Bollinger and Smith, 2001;Hansen et al, 1999;Henriques and Curado, 2009;Lawrence, 2008 Organizational newsletter/newspaperprivate broadsheet for internal distribution Process Curado and Bontis, 2010 Staff mobility (between offices, teams and activities)transferring people between offices, teams and activities Process Chong et al, 2011;Hansen et al, 1999;Kankanhalli et al, 2003;Kong and Thomson, 2009 Storytellingtelling true or fictitious stories Process Kaye and Jacobson, 1999;Riege and Zulpo, 2007 Teamworkactivities carried out in teams Process Bollinger and Smith, 2001;Coakes et al, 2008;Saito et al, 2007;Kong and Thomson, 2009 Trainingindividual or group training, either face-to-face or at a distance analogies, concepts or models . According to Nonaka and Konno (1998), two factors are critical for externalization: (1) conversion of tacit to explicit knowledge using techniques that help individuals to express their ideas with words, with concepts or with visuals; and (2) conversion of tacit knowledge from customers and experts into explicit knowledge.…”
Section: Processmentioning
confidence: 99%
“…This team develops a relationship based on trust among all members (managers and subordinates) and that relationship fosters the sharing of tacit knowledge that is appropriate for participating in highly competitive environments. Over time the manager becomes a mentor who holds the knowledge of the firm and works as a knowledge repository available to facilitate the work of the other employees (Henriques and Curado, 2009).…”
Section: Resultsmentioning
confidence: 99%